'Rape is a huge issue in this country': Discursive constructions of the rape crisis in South Africa. (November 2013) - Dosekun, Simidele
This article considers how the issue of rape in South Africa is discursively constructed by women who have not experienced it. Taking a feminist discursive analytic approach to data from 15 semi-structured interviews, the article identifies four interpretative repertoires which the women used in their talk of rape. These are the statistics repertoire, invoking putatively objective rape statistics; crime repertoire, locating rape within a crisis of crime; race repertoire, naming the racial Other as the rapist; and gender repertoire, explaining rape in terms of normal gendered dynamics and practices. The women chiefly deployed the statistics, crime and race repertoires. These repertoires intersected to construct rape as horrifically prevalent in South Africa yet concerning a classed, raced and spatially-distanced 'Other'. They also elided a focus on the gendered scripts and power relations which South African feminists implicate centrally in what they deem a national rape crisis.